2020
DOI: 10.21203/rs.3.rs-16665/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innovating Editorial Practices: Academic Publishers at Work

Abstract: Abstract Background: Triggered by a series of controversies and diversifying expectations of editorial practices, several innovative peer review procedures and supporting technologies have been proposed. However, adoption of these new initiatives seems slow. This raises questions about the wider conditions for peer review change and about the considerations that inform decisions to innovate. We set out to study the structure of commercial publishers’ editorial process, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Short‐staffed editorial teams . Horbach and Halffman (2020) observed that many academic journals in China had small editorial offices with only a few editors, a simple staff structure, and little task specialization while, by contrast, the large international publishers featured a highly specialized division of labour and long procedural production chains. The editorial offices of journals, then, are often short‐staffed in China, with relatively few individuals being responsible for everything from the screening of preliminary manuscripts and the second review to copyediting, proofreading, and distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Short‐staffed editorial teams . Horbach and Halffman (2020) observed that many academic journals in China had small editorial offices with only a few editors, a simple staff structure, and little task specialization while, by contrast, the large international publishers featured a highly specialized division of labour and long procedural production chains. The editorial offices of journals, then, are often short‐staffed in China, with relatively few individuals being responsible for everything from the screening of preliminary manuscripts and the second review to copyediting, proofreading, and distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we also propose community-led experimentation with new technologies for peer review, albeit in ways other than the simplistic technological fixes offered by commercial publication infrastructure. To be sure, infrastructural tools are useful to tackle well-defined issues like plagiarism (Horbach and Halfmann 2020), but they are of very limited use in assisting editors with more substantive tasks such as reviewer match-making. We specifically propose to think about technological possibilities for establishing new forms of gift exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Such literature is often produced by scientific practitioners with a personal interest in addressing shortcomings of peer review; for example, failure to detect misconduct or bias (Abramowitz, Gomes, and Abramovitz 1975;Peters and Ceci 1982;Weller 2002). Rather than focusing on aberrations from a posited epistemological norm, STS scholars have tended to analyze peer review as constitutive of and legitimating particular forms of interaction between authors, editors, and reviewers (Hackett and Chubin 1990;Hirschauer 2010Hirschauer , 2015Pontille and Torny 2014;Horbach and Halffman 2020;Horbach 2019;Eve et al 2021;Siler and Strang 2017). Despite these efforts, the political-economic organization of peer review remains understudied, both in regard to the labor it draws on and in terms of how scholarly publishing as a business mediates its epistemic workings.…”
Section: The Peer Review System As a Gift Economymentioning
confidence: 99%
“…Separate models are estimated for first-versus aggregate-author characteristics. 11 Author gender (cf. H2) is captured by a dummy variable taking value 1 if an author is female, and 0 otherwise.…”
Section: Measurementmentioning
confidence: 99%